2017
DOI: 10.17576/jkmjc-2017-3301-23
|View full text |Cite
|
Sign up to set email alerts
|

Transforming Political Advertising in Malaysia: Strategizing Political Advertisements towards First-Time and Young Voters in Malaysian GE 14

Abstract: Undoubtedly, the 2013 Malaysia's general election campaign marked to have significantly increased in budget, and much was contributed to advertising. The general election 2013 was noted to be among the most interesting campaign, with salient competitive campaign among the two coalition political parties. This research aims at analyzing the 2013 political advertisements rendered during the time, in order to give insights as to transform and strategize the next 2018 General Election advertising campaign. The kin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…The new voters' motivations are reflected in their willingness to use their ballots to address these problems so that Malaysia may advance under the direction of the next prime minister. Similar to the above, Abd Rahim et al (2017) also came to an agreement that solving problems is what drives young Malaysian voters to cast ballots. They discovered that young Malaysian voters frequently assess how well political parties handle challenges or follow through on election-related pledges (Abd Rahim, et al, 2017).…”
Section: Reasons For Young Voters To Votementioning
confidence: 74%
See 1 more Smart Citation
“…The new voters' motivations are reflected in their willingness to use their ballots to address these problems so that Malaysia may advance under the direction of the next prime minister. Similar to the above, Abd Rahim et al (2017) also came to an agreement that solving problems is what drives young Malaysian voters to cast ballots. They discovered that young Malaysian voters frequently assess how well political parties handle challenges or follow through on election-related pledges (Abd Rahim, et al, 2017).…”
Section: Reasons For Young Voters To Votementioning
confidence: 74%
“…Similar to the above, Abd Rahim et al (2017) also came to an agreement that solving problems is what drives young Malaysian voters to cast ballots. They discovered that young Malaysian voters frequently assess how well political parties handle challenges or follow through on election-related pledges (Abd Rahim, et al, 2017). They used qualitative research methods to conduct focus group discussions for the new voters in rural, semi-urban, and urban areas of GE14.…”
Section: Reasons For Young Voters To Votementioning
confidence: 74%
“…During the Malaysian election campaigns, political parties target voters with both positive and negative political advertising (de Run & Ting, 2014;Kaid & Holtz-Bacha, 2006;Rahim & Mohamed, 2017). A decade ago, parties used printed materials and television (National broadcaster Radio Television Malaysia -RTM) to disseminate information election campaigns, but now online mediums such as Facebook, blogs, and Twitter take precedence (Chu, 2018;Kaid & Holtz-Bacha, 2006).…”
Section: Young Voters In Malaysiamentioning
confidence: 99%
“…By connecting political parties with their potential voters and communicating policy agendas (McGinnis, 1969;Valentino, Hutchings & Williams, 2004), advertising can make a significant contribution. A recent study by Rahim and Mohamed (2017) revealed that people who possess a low level of participation and political knowledge are more heavily influenced by advertisements. Moreover, Internet advertising was found to have a direct influence on political participation (Weber, Loumakis & Bergman 2003).…”
Section: Introductionmentioning
confidence: 99%